The ontology of globalization: the loss of worlds in the face of rising a uniform globe - Yılmaz, Erdal (Dîvân Disiplinlerarası Çalışmalar Dergisi, 2021)
Up until Kant’s critical philosophy, it was not easy to speak of the “world” itself as distinct from “nature”. After Kant, the world began to be considered from a historical perspective. Therefore, the world came to be considered as historical rather than natural, which is why it is possible to speak of different worlds in the history of thought. However, globalization more and more drives these different worlds into a uniform historical globe. In this paper, I consider the question of globalization as a passage “from multiple historical worlds to a uniform historical globe”. By analyzing the passages from “nature” to the “world” and from the “world” to the “globe,” I focus on how the idea of “dwelling in the world” and of “saving the earth” has increasingly transformed into the idea of “dominating the world” and of “owning the earth”.
Keywords: Nature, World, Globalization, “Dwelling in the world”, “Saving the earth”, “Dominating the world”, “Owning the earth”.; Felsefe (Genel)